Systematic evaluation of combined herbal adjuvant therapy for proliferative diabetic retinopathy - Huai, Baogeng; Huai, Baosha; Su, Zhenghua; Song, Min; Li, Changling; Cao, Yingjuan; Xin, Tao; Liu, Deshan (Frontiers in Endocrinology, 2023)
Objective: To evaluate the efficacy and safety of combined traditional Chinese medicine in the adjuvant treatment of proliferative diabetic retinopathy (PDR) by Meta-analysis. Methods: PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang databases were searched by computer. Random controlled clinical trials (RCTS) using traditional Chinese medicine as adjuvant therapy for proliferative diabetic retinopathy were screened, and Stata16.0 software was used to perform meta-analysis on the final included literatures. Results: A total of 18 studies involving 1392 patients were included. Meta-analysis showed that the clinical effective rate OR=2.99 (CI: 2.18-4.10, I2=42.7%, P<0.05); Visual acuity MD=0.10(CI: 0.06-0.13, I2=0%, P<0.05); Fundus efficacy OR=5.47 (CI: 1.33-22.51, I2=71.4%, P<0.05); Neovascularisation regression rate OR=8 (CI: 3.83-16.71, I2=30.1%, P<0.05); Macular foveal thickness MD=-44.24 (CI: -84.55--3.93, I2=95.6%, P<0.05); Absorption of vitreous hemorrhage OR=4.7 (CI: 2.26-9.77, I2=0%, P<0.05); Fasting blood glucose MD=-0.23, (CI: -0.38--0.07, I2=0%, P<0.05); 2h postprandial blood glucose MD=-0.19 (CI: -0.52-0.14, I2=0%, P=0.25). From the results, the combined Chinese medicine adjuvant therapy showed better efficacy than the control group. A total of 69 kinds of traditional Chinese medicine were involved in 18 studies, among which the top four applied frequencies were Panax notoginseng, Rehmannia rehmannii, Astragalus membranaceus and Poria cocos. Most of the medicines were sweet and bitter in taste, the qi tended to be slight cold and cold, and the meridian tropism belongs to the liver meridian. Conclusion: The combination of traditional Chinese medicine adjuvant therapy has a good curative effect on PDR patients. However, the relevant clinical trials are few and more high-quality clinical trials are still needed, what's more the attention should be paid to the exploration of its safety.